MR IMAGING OF AN EXTRAABDOMINAL DESMOID TUMOR OF THE SUPRACLAVICULAR AREA - SIVASOMBOON, Chate (The ASEAN Journal of Radiology, 2023)
Extraabdominal desmoids are benign but locally aggressive tumors, some of which have the appearance on MRI as malignant neoplasm. A case of a pathologicallyproven extraabdominal desmoid of the left shoulder involving left levator scapulae muscle is presented with discussion of MRI features of the lesion that may help in preoperative radiological diagnosis, along with a review of literature.